2015
DOI: 10.1002/adhm.201400751
|View full text |Cite
|
Sign up to set email alerts
|

Blended Nanoparticle System Based on Miscible Structurally Similar Polymers: A Safe, Simple, Targeted, and Surprisingly High Efficiency Vehicle for Cancer Therapy

Abstract: A novel blended nanoparticle (NP) system for the delivery of anticancer drugs and its surprisingly high efficacy for cancer chemotherapy by blending a targeting polymer folic acid-poly(ethylene glycol)-b-poly(lactide-co-glycolide) (FA-PEG-b-PLGA) and a miscible structurally similar polymer D-α-tocopheryl polyethylene glycol 1000 succinate-poly(lactide-co-glycolide) (TPGS-PLGA) is reported. This blended NP system can be achieved through a simple and effective nanoprecipitation technique, and possesses unique pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…The dynamic light scattering result showed that hydrodynamic sizes of FGC and FGC@DOX were 417 ± 11 and 482 ± 16 nm, respectively (Figure S2, Supporting Information). The hydrodynamic size was larger than that observed via TEM, since TEM was observed under vacuum and samples would be shrinkage . Encapsulation of DOX by FGC was mainly due to the coordination interaction between Fe 3+ centers and deprotonated hydroxyl groups of the aglycone moiety in DOX .…”
Section: Resultsmentioning
confidence: 81%
“…The dynamic light scattering result showed that hydrodynamic sizes of FGC and FGC@DOX were 417 ± 11 and 482 ± 16 nm, respectively (Figure S2, Supporting Information). The hydrodynamic size was larger than that observed via TEM, since TEM was observed under vacuum and samples would be shrinkage . Encapsulation of DOX by FGC was mainly due to the coordination interaction between Fe 3+ centers and deprotonated hydroxyl groups of the aglycone moiety in DOX .…”
Section: Resultsmentioning
confidence: 81%
“…146 Tao et al 147 reported a novel polydopamine-based surface functionalization method to develop aptamer-conjugated NPs for in vivo tumor targeting and finally achieved an enhanced therapeutic effect compared to the unfunctionalized NPs. The Mei group 148 reported a folic acid (FA)-conjugated blended NP system that achieved active targeting of cervical cancer and enhanced the uptake efficiency of FA-NPs compared to unfunctionalized NPs. Alexis et al 149 reported the first example of a targeted NP-affibody bioconjugate for controlled drug delivery to HER-2-positive cancer cells.…”
Section: Physicochemical Properties Of Nanoparticles Affect Their Cmentioning
confidence: 99%
“…Yet, the functionalization of nanomaterials is still regarded as a complex and a delicate process. In some cases, the complete functionalization of nanomaterials' surface does not guarantees an improvement of nanomaterials accumulation in tumors . In fact, targeted nanomaterials demand an appropriate ligand density for accomplishing such purpose.…”
Section: Approaches Used To Improve Nanomaterials Accumulation In Tumorsmentioning
confidence: 99%